Systematic analysis of some Astereae (Asteraceae) species by Integrating pollen morphology and molecular evidence - Qu, Tianmeng; Xie, Gan; Zheng, Xinyi; Chen, Xinyu; Zhang, Yanru; Lu, Lili; Fu, Zhixi (Frontiers in Plant Science, 2025)
Astereae, the second-largest tribe within Asteraceae, includes numerous species of economic and medicinal importance. While comprehensive systematic studies have been conducted on Astereae classification, certain controversies remain unresolved. The taxonomic boundaries between alpine Aster and Erigeron are uncertain due to their morphological similarity, and the systematic placement of Formania mekongensis remains debated. To address these issues, we applied a combination of morphological and molecular phylogenetic approaches. 21 species from 12 genera within Astereae were selected based on a morphological and molecular phylogenetic framework. Sampling, experiments, photography, and measurements were conducted using standardized methods, resulting in 12 pollen trait parameters. These parameters were then used to construct a hierarchical dendrogram of pollen morphology. A molecular phylogeny was constructed based on ITS sequences to further elucidate the systematic relationships among these species. The results revealed that pollen morphology provides valuable insights into subtribal classifications. Significant differences in pollen size and spine morphology were observed between Aster and Erigeron, with the former exhibiting larger pollen grains with long, broad, and sparsely distributed spines. Clustering results also provided the first palynological evidence for placing F. mekongensis within Asterinae. This study underscores the importance of integrating pollen morphology and molecular evidence to refine the classification and phylogeny of Astereae.